Peran Hak Paten dalam Melindungi Inovasi Obat dan Meningkatkan Keberlanjutan Industri Farmasi - Maulana, Adam Afin; Abadi, Suwarno (Universitas Muhammadiyah Ponorogo, 2025)
Patents play a strategic role in the development of the pharmaceutical industry as a mechanism for protecting drug innovation that drives research and development. In Indonesia, patent protection provides a legal basis to ensure exclusive rights to commercialize inventions, guarantee returns on investment, and facilitate the creation of innovative, safe, and quality pharmaceutical products. However, there is a tension between patent protection and the need for public access to affordable medicines. This article aims to analyze the role of patent protection in driving pharmaceutical innovation while evaluating its impact on the sustainability of the industry and public accessibility in Indonesia. This study uses a descriptive analytical method through a review of literature and secondary data relevant to the issues of patent protection, pharmaceutical innovation, and drug access in Indonesia. The analysis was conducted to identify the potential and challenges of implementing the patent system, as well as policies that can balance the need for innovation with public health interests. The results of the study show that although patents are able to attract investment and increase the competitiveness of the Indonesian pharmaceutical industry in the global market, their monopolistic nature often leads to increased drug prices, limiting access for vulnerable groups. Policies such as compulsory licensing can be a solution to ensure the production of generic drugs without neglecting innovation protection. With a balanced approach between intellectual property protection and equal access to essential medicines, Indonesia has the potential to build a sustainable pharmaceutical industry that is able to compete globally while meeting the health needs of its people.